Counseling on the Correct Teeth Brushing Demonstration Method Compared to Leaflets and Posters on Student Debris Index Score at Pondok Labu State Elementary School, Jakarta Selatan - R. E., Pudentiana Rr.; Ngatemi; F., Indrayati,; Hariyanti; Nurhayati (Global Writing Academica Researching and Publishing, 2023)
Children of primary school age, namely the age range of 6 to 12 years, are a vulnerable age group that need attention, because during this period there are primary teeth and permanent teeth simultaneously in the oral cavity. The 2004 Household Health Survey showed people's behavior regarding the habit of brushing their teeth, as many as 91% of the population aged 10 years and over did it every day, but only 7% brushed their teeth at the right time, namely after breakfast and before going to bed at night. This study aims to see the difference between counseling on how to brush your teeth properly with demonstration methods compared to leaflets and posters. This research will be carried out using a quantitative approach. The results of this study then found that the demonstration method had the greatest difference in improvement (60%) compared to leaflets (12%) and posters (24%). This then shows that the demonstration method group has achieved a greater percentage than the poster and leaflet media.